Efektifitas Media Video Pembelajaran terhadap Pemahaman Konsep Matematika Peserta Didik Kelas IV SD Islam Khaira Ummah Padang - Rahmatika, Ulva; Yuliantika, Sonya; Frasandy, Rendy Nugraha (Tarbiyah al-Awlad, 2023)
This research was motivated by students' low understanding of concepts, especially in mathematics learning. One of the reasons for the low understanding of students is the lack of use of learning media in the learning process and educators not using alternative media such as learning video media. Learning video media is an alternative that can be used to attract students' attention to learning. The aim of the research is to determine the effectiveness of using learning video media on understanding mathematical concepts in fourth grade students at Khaira Ummah Islamic Elementary School, Padang. This type of research is quantitative with a quasi-experimental method. This research design is a static two group design. The population used was class IV of SD Islam Khaira Ummah Padang using purposive sampling techniques for sampling. The selected sample consisted of two classes, the experimental class and the control class. The data for this research are the scores for understanding mathematical concepts in fourth grade students at Khaira Ummah Padang Islamic Elementary School using and without using learning video media. The instrument of this research is a test. The analytical requirements tests carried out are the normality test and homogeneity test. The results of this research can be seen from the average score for understanding mathematical concepts without using learning video media for class IV Islamic Elementary School Khaira Ummah Padang, namely 78.70. The average score for understanding mathematical concepts using learning video media for class IV Islamic Elementary School Khaira Ummah Padang is 91.05. Based on the t-test, the results of this tcount are compared with ttable at degrees of freedom (dk) = (n-2) at the 95% significance level. Tcount > Ttable (5.5>1.71) then the hypothesis H0 is rejected and H1 is accepted. Based on the results of this research, it can be concluded that the understanding of mathematical concepts of fourth grade students at Islamic Elementary School Khaira Ummah Padang using video learning media is higher than without using video learning media.